KAJIAN TINGKAT KELAYAKAN SANITASI LINGKUNGAN PERMUKIMAN MLATIBARU KOTA SEMARANG - Nur Sukma; Andarina Aji Pamurti (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2022)
Mlatibaru is one of the settlements located in the District of East Semarang which has an unfavorable environment so it needs to get a lot of attention and handling. A clean and healthy environment can be influenced by the behavior of people living within the scope of that environment. The lack of environmental health in the Mlatibaru settlement is not only influenced by community behavior, but also influenced by several factors such as a less than optimal sanitation system, namely the drainage system (waste water), clean water, solid waste, and waste management, which can reduce the feasibility of the system. sanitation and cause environmental pollution. Because the availability of the sanitation system does not have to run properly, there will always be problems. Where as a result, besides being able to reduce the feasibility of sanitation, it can also cause environmental pollution such as tidal flooding. The purpose of this study is to examine the sanitation conditions such as the drainage system (wastewater), clean water, solid waste, and waste management as well as how the level of sanitation in the Mlatibaru settlement area is. This study uses quantitative methods. With the method of data collection observation, interviews, questionnaires, and documentation. The results of the study of the feasibility level of sanitation in Mlatibaru settlements are the drainage system (wastewater) which is included in the moderate level, clean water is included in the high feasible level, solid waste is included in the low feasible level, and waste management is included in the moderate feasible level. So in this case, it is necessary for the community to have an active role in improving the quality of sanitation provision to continue to improve the health of the residential environment.